The Role of The Notary Code of Ethics and Notary Legislation Against Notaries Who Commit Criminal Acts of Fraud and Embezzlement (Case Study Court Decision Surabaya No 2200/PID.B/2020/PN SBY) - Prima Dienta Putra; Mohamad Fajri Mekka Putra (IHSA Institute, 2022)
This study discusses the Surabaya District Court Decision Number 2200/Pid.B/2020/PN SBY to analyze the Notary Code of Ethics role and other laws and regulations against Devi Chrisnawati, who committed fraud and embezzlement of money. Devi Chrisnawati, where Devi Chrisnawati promises the victim a 5% profit if the victim lends money to Devi Chrisnawati. Devi Chrisnawati was then proposed to be dishonorably dismissed by the Central Supervisory Council because Devi Chrisnawati committed fraud and embezzlement while still serving as a Notary in the city of Surabaya. The fraud and embezzlement committed by Devi Chrisnawati have violated Article 6, paragraph (1) of the Notary Code of Ethics.